A killing frost - Marsden, John, 1950-; Marsden, John, 1950- (New York, NY : Scholastic Inc., 1999)
Ellie and her friends, a small band of teenagers trying to survive in the Australian countryside, continue to resist the enemies who have invaded their country.
"Laurel-leaf book."
"First published 1995 by Pan Macmillan Australia Pty Ltd. under the title The third day, the frost"--T.p. verso.
Sequel to: Tomorrow, when the war began and The dead of night.
Keywords: Survival -- Fiction; War stories; Australia -- Fiction; Adventure stories; War stories; Young adult fiction